If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 50 = 6x Reorder the terms: 50 + 3x = 6x Solving 50 + 3x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 50 + 3x + -6x = 6x + -6x Combine like terms: 3x + -6x = -3x 50 + -3x = 6x + -6x Combine like terms: 6x + -6x = 0 50 + -3x = 0 Add '-50' to each side of the equation. 50 + -50 + -3x = 0 + -50 Combine like terms: 50 + -50 = 0 0 + -3x = 0 + -50 -3x = 0 + -50 Combine like terms: 0 + -50 = -50 -3x = -50 Divide each side by '-3'. x = 16.66666667 Simplifying x = 16.66666667
| 2x^2-8x-16y-24=0 | | -34+22=-3x+9x | | x-3/5=1/15 | | 44-50=x | | -76=(-2/3) | | 15c-8-3x=16 | | 4x^3+24x^2+36x=0 | | -3.4x-3=-2.9x+2 | | 3x+45=76,5 | | 2x^3-12x^2+18x+45=0 | | 4x^2-9=3x^2 | | d-3=-17 | | -3x+5+4x=-22+19 | | 24t^2-10t-4=0 | | x^2+1=x^2-6 | | -3(4s-3)-9=-2(8s+5)-3 | | 8(a+b)=(a+b)8 | | rx^2+sx+t=0 | | -12+y=24+-9 | | 3x+6=2x^2+4 | | 2x-15=-45 | | 204=20t+16t^2 | | ln(5x-6)-ln(3x-1)=0 | | H=-16t^2+80t+1 | | 2(4+3)+2=-4(x+1) | | -7x+6=-8 | | 9h^2+4=4 | | 2x=4x+8 | | -3(4s-2)-6=-3(9s+3)-5 | | 4x+-22=-2 | | -4.4x-3=-3.9x+2 | | .5-2= |